The Impact of Social Media Marketing on Gen Z Women’s Buying Interest Through Brand Attitude and Brand Equity in Cosmetic Products : - Muhammad Ashdaq; Muhammad Jamil; Nur Fitriayu Mandasari (Manajemen FEB Unima, 2024)
Marketing through social media has become a marketing strategy that is widely used by the cosmetics industry, especially with the number of consumers that continue to grow as generations increase. Generation Z women are a potential market in this industry where this generation is a new entrant consumer. The purpose of this study is to investigate the influence of marketing through social media on the intention to make purchases with variables mediating brand attitude and brand equity on cosmetic products in the city of Makassar. The research was conducted by distributing questionnaires to 288 respondents, selected using a non-probability sampling technique known as convenience sampling. The collected primary data is then processed using the Structural Equation Modelling (SEM) method using AMOS 23 software. The research results indicate that marketing via social media has a positive and significant impact on brand attitude and brand equity but does not significantly influence the purchasing intentions of Gen Z women. Additionally, brand attitude and brand equity do not effectively mediate the relationship between social media marketing and purchase intentions. These findings suggest that cosmetic companies need to refine their social media marketing strategies to better target Gen Z women.